Electrospun luminescent aeolotropic conductive film enabled by a photoactive semiconductor as a conductive and luminescent material. (17th February 2023) - Qi, Haina; Hu, Yaolin; Yang, Liu; Shao, Hong; Ma, Qianli; Li, Dan; Yu, Wensheng; Dong, Xiangting
Graphical abstract: Highlights: Aeolotropic conduction and luminescence are first realized only by using a substance. Conductive aeolotropism is firstly achieved by utilizing photoconductive effect. Photoactive semiconductor is first used to prepare aeolotropic conductive film (ACF). ACF exhibits superior photoconduction and luminescence upon light irradiation. Functional conversions of ACF are easily realized by controlling light irradiation. Abstract: It is a crucial task to design and fabricate the microscopic construction unit for researching and developing polyfunctional novel macroscopic aeolotropic conductive films (ACFs). In this work, {High concentration 2, 7-dibromo-9-fluorenone (H-DBF)/[polyvinylidene fluoride (PVDF) + polyvinylpyrrolidone (PVP)]}//[low concentration DBF (L-DBF)/(PVDF + PVP)] Janus nanofibers as construction units to directionally arrange to form ACF are devised and facilely constructed by a parallel electrospinning technology. ACF consists of a photoactive semiconductor material concurrently as a luminescent and conductive material. H-DBF displays high conductance and weak luminescence, but L-DBF exhibits low conductance and high luminescence. By taking full advantage of traits of DBF, for the first time, high and low concentrations of DBF are utilized and further integrated into the Janus nanofiber (JN), and thus rational design of construction unit is realized at the microscopic level. Under light illumination, the H-DBF side is conductive and the L-DBF side is insulating, resulting in the fact that the arrayed ACF conducts and insulates along the arranged and perpendicular orientation of JNs respectively. Therefore, the ACF has aeolotropic conductivity by adjusting the DBF content on both sides of Janus nanofiber. When there is no light illumination, the ACF does not have electrically conductive aeolotropy and displays insulativity. The ACF realizes the conversion from non-aeolotropic conductivity to aeolotropic conductivity by converting from no light to light illumination. At the same time, because the luminous intensity of L-DBF is stronger than that of H-DBF, the introduction of L-DBF side can improve the luminous intensity of the ACF and achieve excellent versatility, realizing visualization effect. ACF reveals green luminescence under light illumination. To our knowledge, this is the first time that the sample has tunable aeolotropic conductivity and luminescence by only adjusting the content of a substance. The devising conception and technique play an essential role to develop new-typed ACFs with polyfunction.